(untitled) - Tolkien, J. R. R. (New York, 2002)
While the evil might of the Dark Lord Sauron swarmed out to conquer all Middle-earth, Frodo and Sam struggled dep into Mordor, seat of Sauron's power. To defeat the Dark Lord, the accured Ring of Power had to be destroyed in the fires of Mount Doom...
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy